A critique of the concept of critical juncture: the question of change in Historical Institutionalism - Mariano, Marcelo Passini [UNESP]; Ferreira, Guilherme Augusto Guimarães; Neves, Bárbara Carvalho [UNESP] (FapUNIFESP (SciELO), 2023)
Introduction This article addresses the divergences around the definition and use of the concept of “critical juncture”. It points to the need to advance its theoretical-conceptual development to broaden the ability of the notion to identify the occurrence of critical junctures. Materials and methods: From a detailed review of the literature of Historical Institutionalism, considering the reference texts and authors of this field in national and international academic repositories, we present a critique of the potentialities and lim-itations of the concept of critical juncture for explaining moments of change. Results: Seeking to overcome the assumed causality between critical juncture and change, this article proposes to reinterpret the concept of critical juncture from the idea of con-tingency, characterizing it as a period of reduction of institutional constraints in which significant changes are possible, although not necessary. Discussion: In a context marked by political-institutional crises, by transformation in the forms of social interaction and by growing instability in various parts of the globe, it is increasingly important to identify and understand periods of crisis of expecta-tions and uncertainty about the future. We argue that the concept of critical juncture, if redefined, as it is done in this article, expands the theoretical model's ability to identify the occurrence of critical junctures, as well as whether they have occurred, are occurring, or will occur. At the same time, this operation helps to explain what would be the necessary causes for institutional change to occur or not
Uma crítica do conceito de conjuntura crítica: a questão da mudança no Institucionalismo Histórico
Keywords: critical juncture; historical institutionalism; institutional change; political change; political institutions